Pengaruh Pengungkapan CSR dan Tingkat Likuditias Pada Agresivitas Pajak Dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Pramana, Ida Bagus Ngurah Indra; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p10, 2019)
This study aims to obtain empirical evidence regarding the effect of CSR disclosure and the level of liquidity with institutional ownership as a moderating variable. This research was conducted at mining sector companies listed on the Indonesia Stock Exchange in 2014-2017. The method of determining the sample used was purposive sampling. The number of samples obtained is 32. The data analysis technique used is the Moderated Regression Analysis (MRA) test. Based on the results of the study found that the level of liquidity has a positive effect on tax aggressiveness, institutional ownership can weaken the influence of the level of liquidity on tax aggressiveness, CSR disclosure does not affect tax aggressiveness, institutional ownership cannot moderate CSR disclosure on tax aggressiveness. further researchers and can provide additional information for the government before determining policies, especially in the field of taxation. Keywor ds: CSR, level of liquidity, institutional ownership